2017
DOI: 10.7567/jjap.56.07je10
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of ultrasonic atomization for dust control in underground mining

Abstract: This study examined dust suppression using water particles generated by ultrasonic atomization (2.4 MHz) at low temperature (10 °C). Green tuff (4 µm), green tuff (6 µm), kaolin, and silica were used as dust samples. Even though ultrasonic atomization makes fine water particles, raising relative air humidity immediately was difficult at low temperature. However, remaining water particles that did not change to water vapor contributed to suppression of dust dispersion. Additionally, the effect of water vapor am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Most of ultrasonic atomizers operate in the piezoelectric driving mode, as this mode yields low energy consumption, high efficiency, simple structure, small atomized particles and low cost [2] , [3] , [4] , [5] . Therefore, ultrasonic atomizers are widely used in the aerospace and medical fields, engines, solid-state batteries, food, and environmental improvement and quality of life improvement applications [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Most of ultrasonic atomizers operate in the piezoelectric driving mode, as this mode yields low energy consumption, high efficiency, simple structure, small atomized particles and low cost [2] , [3] , [4] , [5] . Therefore, ultrasonic atomizers are widely used in the aerospace and medical fields, engines, solid-state batteries, food, and environmental improvement and quality of life improvement applications [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Ultrasonic atomization is generated owing to capillary waves on the liquid surface and ultrasonic cavitation [4][5][6] in the liquid. Ultrasonic atomization is applied to several fields such as humification, aroma diffusion, dust control, 7) and nanoparticle separation. 8) In 2001, Sato et al reported that ultrasonic atomization enriched ethanol from an aqueous solution.…”
mentioning
confidence: 99%
“…© 2019 The Japan Society of Applied Physics Supplementary material for this article is available online A tomization using ultrasonic vibration has been performed for nearly 100 years; 1,2) however, the generation mechanism of atomization is a historical challenge that has not been elucidated completely, [3][4][5][6][7] and three hypotheses have been developed: surface wave theory, 2,8,9) cavitation theory, [10][11][12][13] and boiling theory. 6,7,14,15) The progress of atomization techniques is very rapid and diverse, and they are widely disseminated not only in industry [16][17][18][19][20] but also in daily life. 21,22) For example, J.…”
mentioning
confidence: 99%